2012
DOI: 10.1590/s0034-70942012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos efeitos da infiltração com bupivacaína, lidocaína e tramadol na cicatrização de feridas em ratos

Abstract: Summary: Hancı V, Hakimoğlu S, Özaçmak H, Bektaş S, Özaçmak HS, Özdamar ŞO, Yurtlu S, Turan IÖ -Comparison of the Effects of Bupivacaine, Lidocaine, and Tramadol Infiltration on Wound Healing in Rats. Background and objectives:The aim of this study was to investigate the effects of saline solution, bupivacaine, lidocaine and tramadol infiltration on wound healing in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
3
1
Order By: Relevance
“…In the study by Fedder et al (26) , the in vitro cytotoxic effect of lidocaine on the proliferation of human fibroblasts was dependent on the concentration of the anesthetic used. The results reported by Fedder et al (26) corroborate the justification that the present study presents different results from those of Rodrigues et al (10) and Hanci et al (21) due to the different concentrations of lidocaine used. However, similar results were reported by Drucker et al (20) , in which no significant difference was observed in collagenization, and by Harris et al (27) , who did not find a cytotoxic effect or a significant reduction in proliferation in cultures of fibroblasts treated with lidocaine.…”
Section: Microscopic Evaluationsupporting
confidence: 90%
See 4 more Smart Citations
“…In the study by Fedder et al (26) , the in vitro cytotoxic effect of lidocaine on the proliferation of human fibroblasts was dependent on the concentration of the anesthetic used. The results reported by Fedder et al (26) corroborate the justification that the present study presents different results from those of Rodrigues et al (10) and Hanci et al (21) due to the different concentrations of lidocaine used. However, similar results were reported by Drucker et al (20) , in which no significant difference was observed in collagenization, and by Harris et al (27) , who did not find a cytotoxic effect or a significant reduction in proliferation in cultures of fibroblasts treated with lidocaine.…”
Section: Microscopic Evaluationsupporting
confidence: 90%
“…Histological analysis of fibroblast proliferation and collagenization revealed possibly delayed healing in the GS and GL animals; however, this was not confirmed by the statistical analysis of the data, which was insufficient to create an unfavorable final result that could impede the surgical healing process. These results contradict those of Rodrigues et al (10) , Hanci et al (21) , and Shekho et al (18) , who reported an effect of lidocaine on collagenization in rats.…”
Section: Microscopic Evaluationcontrasting
confidence: 78%
See 3 more Smart Citations